GUIDELINES FOR SAMPLING AND PRESERVATION OF BLACK FLIES (DIPTERA: SIMULIIDAE) – AN ATTEMPT TO STANDARDIZE FIELD AND LABORATORY PROCEDURES (Acta Entomologica Serbica, 2023)
This paper provides guidelines for sampling and preserving black flies (Diptera, Simuliidae), aiming to standardize field and laboratory procedures. The authors detail the methods for processing black fly samples, from collection to identification, for each stage. They also propose a sampling protocol that considers various environmental factors influencing species distribution and abundance. The paper is based on the authors' personal experience and aims to contribute to a broader understanding of black fly ecology and taxonomy.